2006
DOI: 10.1002/ajim.20316
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lung cancer from exposure to dusts and fibers in Leningrad Province, Russia

Abstract: The study showed increased lung cancer risk for selected categories of DFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 14 publications
1
9
1
Order By: Relevance
“…The evidence for an association between flax dust and fibre exposure and lung cancer risk is limited. One population-based case-control study in Russia shows increased lung cancer risk for linen dust exposure: the age and smoking-adjusted ORs were 3.68 (95% CI 1.00 to 13.6) 9. The risk of non-melanoma skin cancer in our study was reduced in spinning-weaving workers.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The evidence for an association between flax dust and fibre exposure and lung cancer risk is limited. One population-based case-control study in Russia shows increased lung cancer risk for linen dust exposure: the age and smoking-adjusted ORs were 3.68 (95% CI 1.00 to 13.6) 9. The risk of non-melanoma skin cancer in our study was reduced in spinning-weaving workers.…”
Section: Discussioncontrasting
confidence: 41%
“…For flax dust, the data available on the exposure-effect relationships are more limited than data for cotton. In earlier studies of workers exposed to flax fibres, a reduced risk of all cancers,8 and an excess risk of lung cancer was observed 9…”
Section: Introductionmentioning
confidence: 87%
“…The studies originated from Belgium,55 Canada,42 69 99 109 Chile,59 China,48 67 79 106 111 113 114 England,84 Finland,30 74 Holland,76 India,63 Iran,68 Norway,75 Pakistan,81 Poland,105 Russia,34 Sweden,72 86 Uruguay52 and the USA 35 36 38–40 73 78 88 102 110. Overall, a significantly increased risk for developing lung cancer following wood dust exposure was observed (RR 1.25, 95% CI 1.11 to 1.41, n=38), with ‘considerable’ heterogeneity between studies (I 2 =82.1%, p<0.01; figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine publications from 23 studies reported on risk of lung cancer with quantitative assessment of exposure. Thirteen of these studies were excluded because of differences in quantitative assessment of exposure (Appendix 2, [21][22][23][24][25][26][27][28][29][30][31][32][33]). The primary reviewers finally agreed to include 12 articles [34][35][36][37][38][39][40][41][42][43][44][45] reporting on 10 studies (4 cohort studies [34][35][36][37] and 6 case-control studies [38,39,[42][43][44][45]).…”
Section: Resultsmentioning
confidence: 99%